THE IMPACT OF AGING ON SALIVARY FUNCTION AND SALIVARY GLANDS IN OLDER ADULTS: A LITERATURE REVIEW - Susanna Halim; Nadia Putri Sania (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
The aging process is a progressive biological phenomenon that triggers a decline in functional capacity in various organ systems, including the salivary glands, which play a vital role in maintaining oral homeostasis through lubrication and antimicrobial protection. The primary focus of this study is to synthesize scientific evidence regarding the impact of aging on anatomical changes, secretory performance, and biochemical and microbiological shifts in saliva in the elderly. The research steps were conducted through a systematic literature review of reputable scientific sources, including observational and experimental studies, and meta-analyses involving over fifty thousand patients in selected registry data. The study findings demonstrated morphological acinar degeneration and increased connective tissue deposition. Functionally, the majority of elderly individuals experienced decreased salivary flow rates and increased inflammatory mediators such as interleukin-6, which are associated with susceptibility syndrome. The data demonstrated a discrepancy between the subjective perception of xerostomia and the objective outcome of hyposalivation, where Candida albicans colonization was found to increase with the decline in salivary protective function. The main conclusion confirms that salivary gland disorders in the elderly are clinically significant conditions requiring an integrated diagnostic and therapeutic approach, not simply a normal consequence of aging. This in-depth understanding is crucial for healthcare professionals to optimize comprehensive oral health care strategies to sustainably improve the quality of life for the elderly population for a more prosperous future.